Source of resistant against Fusarium wilt and Stemphylium blight in lentil (Lens culinaris Medikus) - Yadav, N.K.; Ghimire, S.K.; Shrestha, S.M.; Sah, B.P.; Sarker, A.; Sah, S.K. (International Journal of Applied Sciences and Biotechnology, 2017)
The crop yield of lentil is below attainable levels which are mainly attributed to pathological factors especially lentil wilt caused by Fusarium oxysporum f.sp. lentis and Stemphylium blight caused by Stemphylium botryosum .Fusarium wilt is a potential threat to letil production not only in Nepal but worldwide that can cause complete crop failure. While stemphylium blight is recently being serious problem to Bangladesh, Nepal and India. In Nepal, multiple disease resistance work was not reported in lentil before the present study. Two trials separately using 185 genotypes were conducted to study the wilt and stem phylium blight were conducted. For wilt screening one hundred eighty five lentil lines including resistant check ILL7164 and susceptible check sindur, were sown in a previously developed wilt sick bed, while for stem phylium blight serarate trial was conducted in the research area of Regional Agricultural Research Station Nepalgunj using augmented design. Natural inoculums were also relied upon. Disease severity data were recorded. Results revealed that incase of Fusarium wilt sixteen genotypes were found resistant and twenty-three moderately resistant while in case of Stemphylium blight 87 resistant and 36 moderately resistant in field condition. It also indicated that 9 genotypes i.e RL-13,RL-21,ILL6468,ILL9996,\ILL6024,ILL6811,ILL7164,Arun,Maheswar bharti showed combined resistant to both the diseases.Int. J. Appl. Sci. Biotechnol. Vol 5(1): 102-107